2013
DOI: 10.1007/s11764-013-0299-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of comorbidity on Health-Related Quality of Life among cancer survivors: analyses of data from the PROFILES registry

Abstract: Cancer survivors suffering from comorbid diseases experience lower levels of health-related quality of life. Clinicians should become more aware of the impact of comorbidity on HRQoL and provide necessary psychological support to assist self-management of comorbid diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 40 publications
17
67
0
Order By: Relevance
“…However, our results are broadly consistent with the few studies conducted in patients with other hematologic malignancies (mainly Hodgkin's and non-Hodgkin's lymphoma patients) indicating the negative impact of comorbidities on patients' HRQOL [26][27][28].…”
Section: Discussionsupporting
confidence: 91%
“…However, our results are broadly consistent with the few studies conducted in patients with other hematologic malignancies (mainly Hodgkin's and non-Hodgkin's lymphoma patients) indicating the negative impact of comorbidities on patients' HRQOL [26][27][28].…”
Section: Discussionsupporting
confidence: 91%
“…Patients with more comorbidities reported higher average pain scores before RT. Previous studies of patients with HNC 50 and heterogeneous cancer diagnoses 39,52,55 reported similar results. This finding may be associated with the co-occurrence of other painful conditions (eg, neck/back pain, osteoarthritis).…”
Section: Predictors Of Each Pain Characteristicsupporting
confidence: 73%
“…Similarly, other studies have reported that increasing number of comorbid conditions were associated with fatigue [22]. We previously found that comorbidity explained a greater proportion of the variance in fatigue scores than clinical or socioeconomic demographic variables [39].…”
Section: Fatigue Variationsmentioning
confidence: 51%